PULL AND BENDING FORCE USING FIBERGLASS WR EPOXY COMPOSITE MATERIALS AND FIBER CARBON EPOXY - Alphario Rachmatino Yudiana (Vortex, 2021)
Bending testing is carried out in the lab. Nurtanio Adisutjipto College of Technology Yogyakarta uses the Gotech Testing Machine INC (Universal Testing Machine) UTM testing machine where the results obtained in the test are in the form of a graphic in which the maximum load value, elastic modulus, area, yield point and span have been obtained. From the results of these tests, we can compare the average value of the maximum load and the modulus of elasticity received in each specimen with variations in carbon fiber and WR fiberglass.